ANALISIS TINGKAT KEMANDIRIAN DAN EFEKTIVITAS PENDAPATAN ASLI DAERAH PADA PEMERINTAH KOTA/KABUPATEN DI PROVINSI JAWA TIMUR TAHUN 2012 – 2016 - Rossid, Andik Achmat; Hidayat, M. Taufik (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACTThis study aims to determine the level of independence and effectiveness of local revenue in the City / Regency Government in East Java Province from 2012 to 2016. The sample of this study was 38 City / Regency Governments. This research data comes from the 2012-2016 budget realization report obtained from the Central Bureau of Statistics website. The analytical method used is the ratio of independence and effectiveness ratio of local revenue. The results show that: From the analysis of the Independence Ratio it can be said that it is very low, it is known that 33 Cities / Regencies are in a ratio between 0% -25% this happens because the Regional Government still depends on the Central Government. It is known that only the city of Surabaya is truly independent in implementing regional autonomy with a ratio of 180.84%. 4 Other cities / regencies are known to be low and moderate with a ratio between 25% -75%. Judging from the PAD Effectiveness Ratio, there are still many that are said to be quite effective, which means that the City / Regency have not been able to achieve the PAD target set, it is known that there are 19 Cities / Regencies. However, almost half of them have a very effective ratio, it is known that there are 16 cities / regencies showing that the government is able to achieve more than the target set. 3 Other cities / regencies are known to be ineffective and have not maximized the potential of the region.